Cerebral processing of emotions in phantom eye pain patients: An event related potential study - Lixia Lou; Yijie Wang; Bingren Zhang; Yanli Jia; Wei Wang; Juan Ye (Advances in Ophthalmology Practice and Research, 2022)
Purpose: Phantom eye pain (PEP) is a major clinical problem after eye removal with no standard treatment protocol to date. As pain is a multidimensional experience associated with emotional and cognitive components, this study aimed to explore the possible neuropsychological mechanisms of PEP in a perspective of emotional cognition, in order to provide a basis for clinical treatment. Methods: Visual oddball event-related potentials (ERPs) under different external emotional stimuli (Disgust, Fear, Sadness, Happiness, Erotica and Neutral) were tested in 12 patients and 12 healthy volunteers. Participants' affective states were measured with the Mood Disorder Questionnaire (MDQ), the Hypomania Checklist-32 (HCL-32), and the Plutchik–van Praag Depression Inventory (PVP). The amplitudes and latencies of N1, P2, N2 and P3 components were analyzed by three-way ANOVA, i.e., group (2) ​× ​emotion (6) ​× ​electrode (3). Multiple comparisons were performed using Bonferroni's test. Results: Longer N1 latencies, increased N1 amplitudes; shorter P2 latencies under Disgust and Happiness, decreased P2 amplitudes; shorter N2 latencies under Erotica, increased N2 amplitudes were found in patients compared with controls. There was no main effect of group or interaction effect on P3 latencies and P3 amplitudes. The MDQ and HCL-32 scores were lower, and the N1 latencies under Sadness were negatively correlated with PVP scores in patients. Conclusions: PEP patients showed reversed patterns in exogenous attention allocation and enhanced involuntary attention to emotional stimuli compared with controls. This study demonstrated cortical processing of emotions in PEP patients and could provide a basis for developing emotional intervention therapy.